Challenges of Deradicalisation, Rehabilitation and Reintegration of Boko Haram Insurgents in Northeast Nigeria - SAMBO, Usman; BUKAR, Hadiza Mali; BURATAI, Hadiza Ali (Indonesia Strategic Sustainability, 2024)
Purpose: For more than a decade, the Boko Haram insurgency has been an internal and external security threat to Nigeria. This study aims to identify challenges and provide policy input to ensure the success of deradicalization and reintegration programs as a pathway to peacebuilding in North Eastern Nigeria.Methodology:This research method adopts a qualitative data collection and analysis strategy, with special interviews using unstructured questionnaires with family members of victims, officials from the North East National Emergency Management Agency, security officers, academics, and officials from international donor organizations.Findings: The findings show that the main obstacles to deradicalization and rehabilitation of repentant Boko Haram members include negative perceptions of victims' families, desire for revenge, suspicion of the authenticity of repentance, accusations of espionage, corruption of public officials, and the inability to provide an environment that supports full reintegration.Implication:These findings impact the importance of practical steps to ensure that surrendering rebels can be productive. At the same time, victims and their families must be adequately compensated to prevent future tendencies toward retaliation and the resurgence of the insurgency.